Changing name of epilepsy in Korea; cerebroelectric disorder (noi‐jeon‐jeung, 뇌전증, 腦電症). Issue 3 (13th January 2014) - Kim, Heung Dong; Kang, Hoon‐Chul; Lee, Sang Ahm; Huh, Kyun; Lee, Byung‐In
Summary Public misconception of epilepsy may lead to significant stigma to the disease itself, thereby causing impaired quality of life in people with epilepsy. Traditionally, epilepsy has been considered to be the consequence of evanescent spiritual forces, and even demonic possession (in many countries). The names of epilepsy in some East Asian countries originated from China, and include madness in their meaning. We recently changed the Korean name of epilepsy, gan‐jil (간질, 癎疾: a crazy, convulsive disease having meaning similar to 癲癎), to a neutral and scientifically explainable name: noi‐jeon‐jeung (뇌전증; 腦電症; cerebroelectric disorder). We expect that changing the stigmatized name of epilepsy to a neutral and scientific term with the meaning of cerebroelectric disorder will reduce the social stigma by understanding of epilepsy as one of the neurologic disorders.